- KLASIFIKASI PENERIMA BANTUAN SOSIAL DI DESA BATUAH MENGGUNAKAN METODE ALGORITMA C4.5 - Nurahman Nurahman; Siti - aminah (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2022)
Batuah Village, Seranau District, Kotawaringin Timur Regency is a village with a difficult economy. The population is increasing, the problems of life are also getting more diverse. Every citizen needs a decent life, so the government held a social assistance program for the residents of Batuah village. This program is expected to help underprivileged families as one of the government's efforts to overcome poverty. Food assistance must be given to people who are entitled to receive it. But sometimes there is still social jealousy caused by the closeness of neighbors and other factors. Other problems that occur include registered residents who have died still receiving assistance, residents who had problems last year still received assistance, and there were residents who received double social assistance. The purpose of this research is to build a simpler role or decision tree to determine the recipients of social assistance. In addition, this study also aims to determine the values of precision, recall, and accuracy. The algorithm used to build the decision tree is Algorithm C4.5. The results of the study using 100 data samples showed that the algorithm's performance reached an accuracy value of 93.00%, a precision value of 100.00%, and a recall value of 65.00%. The performance of the algorithm produced in this study is included in the very good category so that the decision tree resulting from this study can be used as a recommendation to determine social recipients in Batuah village.